What is the role of 360º evaluation in organizational communication? - Mourão, Rita Monteiro (2018)
The performance evaluation and organizational communication have a central role in organizations, because promote organizational effectiveness (Proctor and Doukakis, 2003). Some limitations of top-down performance appraisal (e.g. subjectivity) and new technologies (i.e., intranet) have been urging other evaluations, like 360o evaluation (Kondrasuk, 2012). This is a specific evaluation that considers more than one appraiser (Brutus and Gorriti, 2005). We intend to realize what type of communication that leaders adopt (i.e., support communication or defensive communication) after applying the 360o evaluation. We intend to realize, too, which might be the consequences of this type of communication for some attitudes and behaviors of employees (e.g. commitment, satisfaction, trust and cynicism). To construct a research question, firstly it becomes pertinent to conducting an exploratory qualitative study, through interviews with experts. In theoretical terms, we will present some categories and sub-categories constructed with data from the exploratory interviews (e.g. “360o evaluation as advantageous for organizational communication”). In general, we conclude that 360o evaluation may increase an active voice of employees and promotes a bi-directional and a symmetrical communication among them. In practical terms, the aim is a promotion of the application of 360o evaluation and organizational communication, exceeding any limitations of existing communicative and evaluative processes.